2020
DOI: 10.1371/journal.pone.0231442
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of misdiagnosis of cardiac channelopathies as epilepsy

Abstract: Introduction Cardiac channelopathies are a frequent cause of sudden cardiac death (SCD) and often manifest with convulsive syncope, leading to a misdiagnosis of epilepsy. We aim to evaluate the clinical impact of epilepsy misdiagnosis in a cohort of patients with cardiac channelopathies. Methods Fifty probands/families with a cardiac channelopathy were included. We retrospectively collected information from medical records to identify all patients who presented with convulsive syncope and were diagnosed with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Second, this study lacked an age‐matched control group to compare the incidence of AVB with that in BrS patients. However, compared with the incidence of high‐risk AVB detected in a population of individuals with syncope and structurally normal hearts who were followed with ILR, the incidence of high‐risk AVB in our BrS patients was lower 3–5,12 . Continuous monitoring with ILR was not performed in all patients in this study.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Second, this study lacked an age‐matched control group to compare the incidence of AVB with that in BrS patients. However, compared with the incidence of high‐risk AVB detected in a population of individuals with syncope and structurally normal hearts who were followed with ILR, the incidence of high‐risk AVB in our BrS patients was lower 3–5,12 . Continuous monitoring with ILR was not performed in all patients in this study.…”
Section: Discussionmentioning
confidence: 70%
“…However, arrhythmic syncope can be caused by bradycardia such as atrioventricular block (AVB), which should be managed by cardiac pacing. Despite the fact that high‐risk AVB could be detected in 5%–11% of patients with syncope and structurally normal hearts, 3–5 the clinical characteristics and prevalence of high‐risk AVB in BrS patients with syncope remain unknown. The purpose of this study was to investigate the clinical characteristics of BrS patients with high‐risk AVB.…”
Section: Introductionmentioning
confidence: 99%
“…Petkar et al, found a high incidence of bradyarrhythmias and asystole in cases where there was uncertainty surrounding the diagnosis of epilepsy [37]. Cardiac channelopathies often manifest with convulsive syncope, leading to a misdiagnosis of epilepsy which puts these patients at risk of developing serious and life-threatening arrhythmias [40]. Differentiation of generalised epileptic seizures and syncope can also be quite challenging in veterinary medicine, since the two syndromes can share a similar clinical manifestation [41,42].…”
Section: Discussionmentioning
confidence: 99%